CRP Is an Activator of Yersinia pestis Biofilm Formation that Operates via a Mechanism Involving gmhA and waaAE-coaD - Liu, Lei; Fang, Haihong; Yang, Huiying; Zhang, Yiquan; Han, Yanping; Zhou, Dongsheng; Yang, Ruifu (Frontiers in Microbiology, 2016)
gmhA encodes a phosphoheptose isomerase that catalyzes the biosynthesis of heptose, a conserved component of lipopolysaccharide (LPS). GmhA plays an important role in Yersinia pestis biofilm blockage in the flea gut. waaA, waaE, and coaD constitute a three-gene operon waaAE-coaD in Y. pestis. waaA encodes a transferase that is responsible for binding lipid-A to the core oligosaccharide of LPS. WaaA is a key determinant in Y. pestis biofilm formation, and the waaA expression is positively regulated by the two-component regulatory system PhoP/PhoQ. WaaE is involved in LPS modification and is necessary for Y. pestis biofilm production. In this study, the biofilm-related phenotypic assays indicate that the global regulator CRP stimulates Y. pestis biofilm formation in vitro and on nematodes, while it has no regulatory effect on the biosynthesis of the biofilm-signaling molecular 3ʹ,5ʹ-cyclic diguanosine monophosphate. Further gene regulation experiments disclose that CRP does not regulate the hms genes at the transcriptional level but directly promotes the gmhA transcription and indirectly activates the waaAE-coaD transcription through directly acting on phoPQ-YPO1632. Thus, it is speculated that CRP-mediated carbon catabolite regulation of Y. pestis biofilm formation depends on the CRP-dependent carbon source metabolic pathways of the biosynthesis, modification and transportation of biofilm exopolysaccharide.